2012
DOI: 10.1111/all.12053
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter, randomized, controlled trial testing the effects of acupuncture on allergic rhinitis

Abstract: Background: The aim of this study was to evaluate the efficacy and safety of acupuncture in the treatment for allergic rhinitis. Methods: This study was a multicenter, randomized, parallel-controlled study. Participants were randomized to either the active acupuncture, sham acupuncture, or waitlist groups. The active and sham acupuncture groups received acupuncture treatment three times per week for 4 weeks. In the sham group, minimal acupuncture at nonacupuncture points was used. The waitlist group did not re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
76
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 36 publications
(44 reference statements)
0
76
2
4
Order By: Relevance
“…In a number of studies, the effectiveness of acupuncture in regard to quality of life and the reduction of medication as well as significant improvements of the clinical symptoms has already been shown [1, 8, 12, 30, 31]. Even though our results did not show any significant differences of the single symptoms, a significant improvement of the symptoms was observed in the total sum scores in both the acupuncture and loratadine groups during the course of the treatment.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…In a number of studies, the effectiveness of acupuncture in regard to quality of life and the reduction of medication as well as significant improvements of the clinical symptoms has already been shown [1, 8, 12, 30, 31]. Even though our results did not show any significant differences of the single symptoms, a significant improvement of the symptoms was observed in the total sum scores in both the acupuncture and loratadine groups during the course of the treatment.…”
Section: Discussioncontrasting
confidence: 60%
“…With a prevalence of 20 to 30%, allergic rhinitis is one of the most frequent atopic diseases in Western Europe [13]. It leads to a decrease of the patients' quality of life [4] and causes great cost for medication and social benefits [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asya'da yapılan yeni çalışmalarda akupunkturun PAR'li hastaların semptom ve yaşam kalitelerinde iyileşme sağladığı bildirilse de, uzun süreli ve daha fazla çalışma gerektiği savunulmaktadır (60). AR tedavisinde akupunktur kullanımı ile ilgili randomize kontrollü çalışmalarda akupunkturun etkisini gösteren yeterli kanıt yoktur (10,24).…”
Section: Akupunkturunclassified
“…Nonetheless, two recent welldesigned studies published in peer-reviewed journals showed some benefit on symptom control compared to sham acupuncture. 20,21 At present, the guidelines state that there is sufficient evidence to recommend acupuncture in patients who express an interest. The AAO-HNS guidelines, however, make no recommendation on the use of Chinese herbal therapy due to limited knowledge and concern about standardization and safety of these medicines.…”
mentioning
confidence: 99%